Concise synthesis of protected (2S,4R)-4-hydroxyornithine - Pandey, Satyendra Kumar; Pandey, Menaka; Kumar, Pradeep (Tetrahedron Letters, 2008)
A short synthesis of the nonproteinogenic amino acid, (2S,4R)-4-hydroxyornithine is described. Starting from racemic benzyl glycidol, the scaffold of the target compound was constructed in high enantio- and diastereoselectivity using Jacobsen's hydrolytic kinetic resolution (HKR) and regioselective opening of an epoxide as key steps. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: Epoxide; Grignard reaction; hydroxyornithine; Jacobsen's HKR; Natural product